Characteristics of Memory B Cells Elicited by a Highly Efficacious HPV Vaccine in Subjects with No Pre-existing Immunity - Scherer, Erin M.; Smith, Robin A.; Simonich, Cassandra A.; Niyonzima, Nixon; Carter, Joseph J.; Galloway, Denise A. (PLoS pathogens, 2014)
Licensed human papillomavirus (HPV) vaccines provide near complete protection against the types of HPV that most commonly cause anogenital and oropharyngeal cancers (HPV 16 and 18) when administered to individuals naive to these types. These vaccines, like most other prophylactic vaccines, appear to protect by generating antibodies. However, almost nothing is known about the immunological memory that forms following HPV vaccination, which is required for long-term immunity. Here, we have identified and isolated HPV 16-specific memory B cells from female adolescents and young women who received the quadrivalent HPV vaccine in the absence of pre-existing immunity, using fluorescently conjugated HPV 16 pseudoviruses to label antigen receptors on the surface of memory B cells. Antibodies cloned and expressed from these singly sorted HPV 16-pseudovirus labeled memory B cells were predominantly IgG (>IgA>IgM), utilized diverse variable genes, and potently neutralized HPV 16 pseudoviruses in vitro despite possessing only average levels of somatic mutation. These findings suggest that the quadrivalent HPV vaccine provides an excellent model for studying the development of B cell memory; and, in the context of what is known about memory B cells elicited by influenza vaccination/infection, HIV-1 infection, or tetanus toxoid vaccination, indicates that extensive somatic hypermutation is not required to achieve potent vaccine-specific neutralizing antibody responses.